Penggunaan Media Objek Langsung Dalam Meningkatakan Keterampilan Menulis Puisi Siswa Kelas VI SD Muhammadiyah Pasir Jaya Cikupa Kabupaten Tangerang - Haerudin Haerudin; Nori Anggraini; Siti Mariyam; Nurfadillah Nurfadillah (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service was carried out in Pasir Jaya Village, Cikupa, Tangerang Regency, in collaboration with grade VI students of Muhammadiyah Elementary School and UMT KKN students in 2024, through training or seminars, these grade VI students of Muhammadiyah Elementary School will improve their poetry writing skills. This training was carried out through workshops where elementary school students received instructions on how to write poetry. The grade VI students of Muhammadiyah Elementary School were very enthusiastic about participating in this program, which helped them hone their poetry writing skills. Through direct object media, students gain an understanding of the techniques involved in making poetry. Students are also given inspiration to write poetry. In order to improve students' poetry writing skills in learning Indonesian, direct object media can be used in grade VI of Muhammadiyah Elementary School, Pasir Jaya Village, Cikupa District, Tangerang Regency, Banten.